2012
DOI: 10.1007/s00280-012-1849-3
|View full text |Cite
|
Sign up to set email alerts
|

The T393C polymorphism of GNAS1 as a predictor for chemotherapy sensitivity and survival in advanced non-small-cell lung cancer patients treated with gemcitabine plus platinum

Abstract: This study suggests that the TT genotype of the GNAS1 T393C polymorphism could be an independent prognostic marker to predict chemotherapy sensitivity, favorable OS and PFS in advanced NSCLC patients with GP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…However, predictive markers for response to this regimen are still limited. Our recent study showed that T393C polymorphism of Gs protein α subunit (GNAS1) gene was a predictor for clinical outcomes in advanced NSCLC patients treated with gemcitabine/platinum (Xie et al, 2012). In the current study, we tried a combination of gene polymorphisms potentially related with the effect of this regimen.…”
Section: Discussionmentioning
confidence: 99%
“…However, predictive markers for response to this regimen are still limited. Our recent study showed that T393C polymorphism of Gs protein α subunit (GNAS1) gene was a predictor for clinical outcomes in advanced NSCLC patients treated with gemcitabine/platinum (Xie et al, 2012). In the current study, we tried a combination of gene polymorphisms potentially related with the effect of this regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, there has been no research demonstrating that activating or inactivating mutations or epigenetic changes of GNAS have prognostic and not diagnostic value. The T393C pleomorphism of the GNAS locus has been identified to have prognostic value in various malignant tumors, including clear cell renal cell carcinoma (29), bladder cancer (30), colorectal cancer (31), epithelial ovarian cancer (32), melanoma (33), glioblastoma (34) and non-small cell lung cancer (35).…”
Section: A B C Dmentioning
confidence: 99%
“…Because of its high fatality (the overall ratio of mortality to incidence is 0.87), large numbers of studies focus on the prevention and treatment of lung cancer. Non-small cell lung cancer (NSCLC) accounts for approximately 85% of all lung cancer cases (Xie et al, 2012). In NSCLC, almost half of the patients have advanced and metastatic disease and have missed the opportunity to have surgery.…”
Section: Introductionmentioning
confidence: 99%